Peran Mahasiswa Dalam Peningkatan Nilai-Nilai Religius Pada Usia Lanjut Di Kelurahan Tipes Kecamatan Serengan Kota Surakarta - Nur Hadi; Nita Nur Samsiyah (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2022)
Tipes is a small village located in the Serengan district close to the city center. In this village there are about 12 mosques. One of the mosques in this village is the Masjid Al Iklhas Dipotrunan RT.02 RW mosque. XII which is one of the densely populated areas in Tipes village which is also bordered by the river and Sukoharjo Regency. Some of the jama'ah of the Al-Ikhlas mosque are also nausealaf. Meanwhile, from data obtained from the local kelurahan, the majority of the surrounding communities work as laborers. Such economic conditions then have an impact on the lack of public attraction to programs and activities implemented in the region, including in the fields of education and religion. The strategy carried out in the effort to implement this activity is to plan and optimize joint activities to follow up on the ideas of thought that arise. From this planning, it will be identified who is coordinating and who should be responsible for each stage of the activity. Then we monitor and evaluate its implementation. Jama'ah Masjid Al-Ikhlas is expected to be actively involved in monitoring and evaluating this effort. With this program, the increase in religious values activities at an advanced age in Tipes village has succeeded in providing benefits to the surrounding community. Not only as a means to draw closer to God, but also as the main factor in increasing the potential of Human Resources (HR). With several programs that we have agendad, this can facilitate the needs of the community in preserving religious culture both through habituation and awareness.